Circadian periodicity in space use by ungulates of temperate regions: How much, when and why?. (2nd July 2018) - Péron, Guillaume; Duparc, Antoine; Garel, Mathieu; Marchand, Pascal; Morellet, Nicolas; Saïd, Sonia; Loison, Anne
Abstract: When they visit and revisit specific areas, animals may reveal what they need from their home range and how they acquire information. The temporal dimension of such movement recursions, that is, periodicity, is however rarely studied, yet potentially bears a species, population or individual‐specific signature. A recent method allows estimating the contribution of periodic patterns to the variance in a movement path. We applied it to 709 individuals from five ungulate species, looking for species signatures in the form of seasonal variation in the intensity of circadian patterns. Circadian patterns were commonplace in the movement tracks, but the amount of variance they explained was highly variable among individuals. It increased in intensity during spring and summer, when key resources were spatially segregated, and decreased during winter, when food availability was more uniformly low. Other periodicity‐inducing mechanisms supported by our comparison of species‐ and sex‐specific patterns involve young antipredator behaviour, territoriality and behavioural thermoregulation. Model‐based continuous‐time movement metrics represent a new avenue for researchers interested in finding individual‐, population‐ or species‐specific signatures in heterogeneous movement databases featuring various study designs and sampling resolutions. However, we observed large amounts of individual variation, so comparative analyses should ideally use both GPS and animal‐borne loggers to augment the discriminatory power and be based on large samples. We briefly outline potential uses of the intensity of circadian patterns as a metric for the study of animal personality and community ecology. Abstract : Movement recursions convey a lot of information about what animals need from their home range and how they acquire information. Here, the authors leverage spectral analyses implemented in the R‐package ctmm to obtain a metric of periodicity in space use that can then be compared across individuals, environments and species. Five ungulate species exhibited circannual variation in circadian periodicity, yielding a population‐specific signature in movement data amidst large individual and temporal variance. Landscape heterogeneity, territorial, antipredator and thermoregulation behaviours explained these signatures.